Method for operating an electrodialysis apparatus for an aqueous solution containing an organic solvent using an electrodialysis apparatus equipped with an anion exchange membrane produced by a crosslinking polymerization method
Patent Information
- Application Number
- JP2024172999
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-10-12
- Filing Date
- 2024-10-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-02
AI Technical Summary
【0010】 本発明によれば、有機溶媒に対するハロゲン化物イオンの選択透過性に優れた電気透析装置の運転方法、および電気透析装置が提供される。
Smart Images

Figure 0007642145000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for operating an electrodialysis apparatus and to an electrodialysis apparatus. [Background technology]
[0002] Various techniques for electrodialysis of wastewater containing iodine have been developed. For example, the technique described in Patent Document 1 is known as this type of technique. The wastewater contains iodide ions (I - In addition to iodine components such as sulfate ions (SO4 2- For example, the wastewater usually contains sulfate ions at a concentration of 1 g / L or more, but below the saturation solubility of sulfate, more commonly at around 20 to 50 g / L. Patent Document 1 describes a method of performing electrodialysis on a stock solution that contains iodine-containing inorganic anions and fluorine-containing inorganic anions and is contained in a desalting compartment, using a monovalent selective anion exchange membrane or the like (Claim 1, Examples, etc. of Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-079318 Summary of the Invention [Problem to be solved by the invention]
[0004] However, as a result of investigations conducted by the present inventors, it was found that the electrodialysis method described in the above Patent Document 1 leaves room for improvement in terms of the selective permeability of halide ions to organic solvents. That is, since it has been generally known that ion exchange membranes are damaged by organic solvents, conventional electrodialysis methods have adopted a pretreatment method in which the organic solvent (organic matter) contained in the waste liquid is burned and removed before electrodialysis, as in Patent Document 1. For these reasons, techniques for performing electrodialysis using an ion exchange membrane in a solution containing an organic solvent have not been fully investigated. [Means for solving the problem]
[0005] The present inventors have furthered their investigations into electrodialysis methods for solutions containing organic solvents, and have found that the selective permeability of halide ions in organic solvents can be improved by employing an anion exchange membrane that is relatively solvent-resistant and by appropriately controlling the density of the ion-selective permeable layer in the anion exchange membrane.
[0006] Based on this knowledge, the inventors conducted extensive research and obtained the following results. It was found that anion exchange membranes produced by the cross-linking polymerization method are less soluble in organic solvents and have solvent resistance compared to anion exchange membranes produced by the casting method. The casting method is a technique in which an ion exchange resin is dissolved or dispersed in a solvent to prepare a casting stock solution, which is then cast onto a substrate film and then dried. The anion exchange membranes produced by the casting method were partially dissolved in organic solvents and could not be used for electrodialysis.
[0007] The density of the ion selective permeable layer is measured by a specified electrodialysis test using sulfate ions (SO4 2- ) versus iodide ion (I - ) transmittance ratio (T I / T SO4 It was found that a stable evaluation can be performed by using T I / T SO4 It has been found that the selective permeability of halide ions to polar organic solvents can be increased by using a highly selective anion exchange membrane having a specific value or more. Based on these findings, the invention was completed.
[0008] According to one aspect of the present invention, there is provided the following method for operating an electrodialysis apparatus and an electrodialysis apparatus.
[0009] 1. A method for operating an electrodialysis apparatus, comprising an electrodialysis step of electrodialyzing an aqueous solution containing halide ions and a polar organic solvent using an electrodialysis apparatus equipped with an anion exchange membrane produced by a crosslinking polymerization method, The aqueous solution contains 200 mg / L or more of iodide ions, In the electrodialysis step, When the anion exchange membrane was subjected to an electrodialysis test using a desalted solution containing iodide ions and sulfate ions, when the iodide ion residual rate in the desalted solution was 5%, the iodide ion (I - ) transmittance (%) is T I , sulfate ion (SO4 2- ) transmittance (%) is T SO4 When we define I / T SO4 The anion exchange membrane has a molecular weight of 3.5 or more. A method for operating an electrodialysis apparatus. 2. A method for operating the electrodialysis apparatus according to 1., comprising the steps of: In the electrodialysis step, A method for operating an electrodialysis apparatus, wherein the polar organic solvent contains an organic solvent having a relative dielectric constant of 5 or more at 25°C. 3. A method for operating the electrodialysis apparatus according to 1. or 2., comprising the steps of: The method for operating an electrodialysis apparatus, wherein the aqueous solution contains 0.1% by mass to 50% by mass of the polar organic solvent. 4. A method for operating the electrodialysis apparatus according to any one of 1. to 3., A method for operating an electrodialysis apparatus, wherein in the electrodialysis step, the concentration of halide ions in the desalted solution at the end point as determined by an absorbance method is 0.5 g / L or more and 5 g / L or less. 5. A method for operating the electrodialysis apparatus according to any one of 1. to 4., comprising the steps of: A method for operating an electrodialysis apparatus, comprising the steps of: obtaining the iodide ions by reducing one or more selected from the group consisting of iodine (I2), iodic acid (HIO3), periodic acid (HIO4), and iodine compounds. 6. A method for operating the electrodialysis apparatus according to any one of 1. to 5., A method for operating an electrodialysis apparatus, wherein the anion exchange membrane comprises a base substrate containing a polyolefin and an ion-selective permeable layer formed on one or both sides of the base substrate. 7. A method for operating the electrodialysis apparatus according to any one of 1. to 6., In the electrodialysis step, The anion exchange membrane includes an anion exchange membrane having an ion exchange capacity change rate of within ±5% before and after immersion treatment in a polar organic solvent having a concentration of 50% by mass. A method for operating an electrodialysis apparatus. 8. A method for operating the electrodialysis apparatus according to any one of 1. to 7., In the electrodialysis step, The anion exchange membrane includes an anion exchange membrane having a water content change rate of within ±20% before and after immersion treatment in isopropyl alcohol having a concentration of 50% by mass, as measured by the Karl Fischer method. A method for operating an electrodialysis apparatus. 9. An electrodialysis apparatus for electrodialyzing an aqueous solution containing halide ions and a polar organic solvent, comprising: A concentration chamber; A desalination chamber, The concentration compartment and the deionization compartment are separated by an anion exchange membrane and a cation exchange membrane produced by a cross-linking polymerization method, The aqueous solution contains 200 mg / L or more of iodide ions, When the anion exchange membrane was subjected to an electrodialysis test using a desalted solution containing iodide ions and sulfate ions, when the iodide ion residual rate in the desalted solution was 5%, the iodide ion (I - ) transmittance (%) is T I , sulfate ion (SO4 2- ) transmittance (%) is TSO4 When we define I / T SO4 The anion exchange membrane has a molecular weight of 3.5 or more. Electrodialysis equipment. Effect of the Invention
[0010] According to the present invention, there are provided an operating method for an electrodialysis apparatus having excellent selective permeability of halide ions to an organic solvent, and an electrodialysis apparatus. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view illustrating an example of the configuration of an electrodialysis device according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a diagram illustrating an example of the configuration of an iodine recovery system according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a flow diagram showing an example of an iodine recovery process according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In all drawings, similar components are given similar reference numerals and their explanations will be omitted as appropriate. Also, the drawings are schematic diagrams and do not correspond to the actual dimensional ratios.
[0013] An outline of the method of operating the electrodialysis apparatus of this embodiment will be described.
[0014] The method for operating the electrodialysis apparatus of the present embodiment includes an electrodialysis step of electrodialyzing an aqueous solution containing halide ions and a polar organic solvent using an electrodialysis apparatus equipped with an anion exchange membrane produced by a crosslinking polymerization method.
[0015] In this embodiment, the anion exchange membrane manufactured by the cross-linking polymerization method is used, and thus the solvent resistance is improved compared to the anion exchange membrane manufactured by the casting method. In a preliminary experiment, it was found that the anion exchange membrane manufactured by the casting method was dissolved in a dimethylacetamide solvent with a concentration of about 50%. Moreover, the electrodialysis device equipped with an anion exchange membrane produced by a crosslinking polymerization method preferably also equipped with a cation exchange membrane produced by a crosslinking polymerization method. In addition, polar organic solvents are highly miscible with water and are expected to cause less damage to the ion exchange membrane than non-polar organic solvents.
[0016] According to the present embodiment, it is possible to realize a method for operating an electrodialysis apparatus having excellent selective permeability of halide ions to a polar organic solvent. In one specific embodiment, one or more kinds of halide ions can be selectively permeated into a concentrated solution while the polar organic solvent remains in an aqueous solution (desalted solution).
[0017] In this embodiment, the halide ion may be, but is not limited to, an iodide ion, a chloride ion, a fluoride ion, a bromide ion, etc. These may be used alone or in combination of two or more kinds. Electrodialysis of an aqueous solution (desalted solution) containing halide ions and a polar organic solvent means (i) permeating at least one type of halide ion into the concentrated solution and / or (ii) leaving at least one type of halide ion in the desalted solution. When two or more kinds of halide ions with different mobilities are used during electrodialysis, it is possible to make the species with higher mobility permeate into the concentrated solution and the species with lower mobility remain in the desalted solution. The order of mobility is iodide ion, bromide ion, chloride ion, and fluoride ion.
[0018] In the first operating method, at least iodide ions can be selectively permeated into the concentrated liquid from an aqueous solution (desalted liquid) containing one or more types of halide ions. In the second operating method, iodide ions and chloride ions can be selectively permeated into the concentrated liquid from an aqueous solution (desalted liquid) containing a plurality of types of halide ions. In the third operating method, it is possible to selectively cause fluoride ions to remain in an aqueous solution (demineralized solution) containing one or more types of halide ions. The method for operating the electrodialysis apparatus of this embodiment may use these effects alone or in combination of two or more of them.
[0019] In one example of the method of operating the electrodialysis apparatus of the present embodiment, when an electrodialysis test is carried out using a desalted solution containing iodide ions and sulfate ions, the anion exchange membrane is 5% iodide ion (I - ) transmittance (%) is T I , sulfate ion (SO4 2- ) transmittance (%) is T SO4 When we define I / T SO4 The anion exchange membrane includes an anion exchange membrane having a selectivity of 3.5 or more (highly selective anion exchange membrane).
[0020] Although the detailed mechanism is unclear, it is speculated that increasing the density of the surface of the anion exchange membrane improves its durability against polar organic solvents and maintains the function of the ion selective permeability layer, thereby increasing the selective permeability of halide ions in polar organic solvents.
[0021] The above T of the anion exchange membrane I / T SO4 The lower limit of is 3.5 or more, preferably 5.0 or more, and more preferably 8.0 or more. This makes it possible to increase the selective permeability of iodide ions even in an environment containing a polar organic solvent. ) The above T of the anion exchange membrane I / T SO4The upper limit is not particularly limited, but may be 300 or less, 200 or less, or 50 or less.
[0022] In the electrodialysis step, the aqueous solution may contain water together with the polar organic solvent. The lower limit of the content of the polar organic solvent in the aqueous solution is, for example, 0.1 mass % or more, preferably 0.5 mass % or more, and more preferably 1.0 mass % or more. On the other hand, the upper limit of the content of the polar organic solvent is, for example, 50% by mass or less, preferably 40% by mass or less, more preferably 30% by mass or less. In this case, the solvent other than the polar organic solvent may be water in part or in whole. From the viewpoint of solubility in water, the carbon number of the polar organic solvent is preferably 3 or less.
[0023] The polar organic solvent is not particularly limited as long as it has a relative dielectric constant of, for example, 5 or more at 25° C., and examples thereof include alcohol-based solvents, amide-based solvents, ketone-based solvents, glycol-based solvents, nitrile-based solvents, sulfoxide-based solvents, etc. These may be used alone or in combination of two or more. Examples of the alcohol solvent include methyl alcohol, ethyl alcohol, isopropyl alcohol, and normal propyl alcohol. Examples of the amide solvent include dimethylformamide, diethylformamide, dimethylacetamide, and N-methyl-2-pyrrolidone. Examples of ketone solvents include formic acid, acetic acid, propionic acid, oxalic acid, malonic acid, succinic acid, maleic acid, fumaric acid, adipic acid, formaldehyde, acetaldehyde, and propionaldehyde. Examples of the glycol solvent include ethylene glycol and diethylene glycol. An example of the nitrile solvent is acetonitrile. The sulfoxide solvent includes, for example, dimethyl sulfoxide.
[0024] Examples of low dielectric organic solvents having a relative dielectric constant of 30 or less at 25° C. include alcohol solvents having 2 to 3 carbon atoms, such as isopropanol (IPA).
[0025] Examples of highly dielectric organic solvents having a relative dielectric constant of more than 30 at 25° C. include amide solvents having 1 to 3 carbon atoms, such as dimethylacetamide (DMAc) and dimethylformamide (DMF).
[0026] In the electrodialysis step, the polar organic solvent may contain the above polar organic solvent having a relative dielectric constant of more than 30 at 25°C and / or the above low dielectric organic solvent having a relative dielectric constant of 30 or less at 25°C.
[0027] The method of operating the electrodialysis apparatus of this embodiment can employ the following modifications. Each modification may be adopted in combination with one or more of the other modifications as long as the effect of the invention is not impaired.
[0028] In addition, an example of a method for operating an electrodialysis apparatus according to another embodiment is one in which, in the above-mentioned electrodialysis step, the anion exchange membrane includes an anion exchange membrane having a thickness swelling ratio of 104% or less, as measured according to the following measurement procedure. (Measurement Procedure) The thickness of the anion exchange membrane was measured before and after immersion in a 50% by mass aqueous dimethylacetamide solution at a liquid temperature of 40° C. for 1 hour. The thickness before the treatment was designated D0, and the thickness after the treatment was designated D 50 Let us assume that. The obtained D0, D 50 The thickness expansion rate of the ion exchange membrane is calculated using the formula: (D 50 Calculate by: / D0) x 100.
[0029] In addition, a modified example of the method of operating an electrodialysis apparatus according to another embodiment is such that, in the above-mentioned electrodialysis step, the electrodialysis apparatus is provided with a cation exchange membrane produced by a cross-linking polymerization method, and the cation exchange membrane has a thickness swelling ratio of 104% or less, as measured according to the above-mentioned measurement procedure.
[0030] According to the findings of the inventors, it has been found that the swelling property of an anion exchange membrane in an organic solvent can be stably evaluated by using the rate of change in membrane thickness (thickness swelling ratio) before and after immersion treatment in a 50% by mass aqueous dimethylacetamide solution as an indicator, and that the selective permeability of halide ions in polar organic solvents can be increased by setting the thickness swelling ratio to be equal to or less than the above upper limit value.
[0031] Although the detailed mechanism is unclear, it is speculated that the function of the ion-selective permeability layer is maintained in anion exchange membranes that are difficult to swell in polar organic solvents, thereby enhancing the selective permeability of halide ions in polar organic solvents.
[0032] The upper limit of the thickness swelling ratio of the anion exchange membrane is 104% or less, preferably 103% or less, and more preferably 102% or less, which allows stable electrodialysis in an environment containing a polar organic solvent. The lower limit of the thickness swelling ratio of the anion exchange membrane is not particularly limited, but is, for example, 96% or more, preferably 98% or more, and more preferably 99% or more.
[0033] The upper limit of the thickness swelling ratio of the cation exchange membrane is, for example, 104% or less, preferably 103% or less, and more preferably 102% or less, which enables stable electrodialysis in an environment containing a polar organic solvent. The lower limit of the thickness swelling ratio of the cation exchange membrane is not particularly limited, but is, for example, 96% or more, preferably 98% or more, and more preferably 99% or more.
[0034] Here, according to the findings of the inventors, it has been found that by appropriately controlling the content of components that are easily soluble in polar solvents and by appropriately controlling the polymerization conditions, such as by suppressing the remaining unreacted components during production by a cross-linking polymerization method, it is possible to set the thickness swelling ratio of the anion exchange membrane or cation exchange membrane within the desired numerical range.
[0035] Here, according to the findings of the present inventors, it has been found that the degree of denseness in the surface dense layer (ion-selective permeable layer) of the anion exchange membrane can be stably evaluated by using the SO4 index measured under the following specified conditions as an index, although the mechanism is unclear. By appropriately controlling this SO4 index, the above T I / T SO4 It becomes possible to set the value in a desired range.
[0036] In another variant, it is preferred to use an anion exchange membrane with monovalent selectivity.
[0037] In another modified example, in the electrodialysis process, the anion exchange membrane may include an anion exchange membrane whose ion exchange capacity changes by within ±5% before and after an immersion treatment in a polar organic solvent having a concentration of 50% by mass.
[0038] In another modified example, in the electrodialysis process, the anion exchange membrane may include an anion exchange membrane whose water content, as measured by the Karl Fischer method, changes by within ±20% before and after an immersion treatment in isopropyl alcohol having a concentration of 50% by mass.
[0039] Moreover, the electrodialysis apparatus of this embodiment is an electrodialysis apparatus that separates an aqueous solution containing halide ions and a polar organic solvent into a concentrated solution containing halide ions and a desalted solution containing a polar organic solvent, and is provided with a concentration compartment, a desalting compartment, and an anion exchange membrane and a cation exchange membrane that separate the concentration compartment from the desalting compartment. This electrodialysis device is the above-mentioned "sulfate ion (SO4 2- ) versus iodide ion (I - ) transmittance ratio (T I / T SO4 ) and / or an anion exchange membrane that satisfies the above-mentioned "thickness swelling ratio." Furthermore, the electrodialysis device may be equipped with a cation exchange membrane that satisfies the above-mentioned "thickness swelling ratio."
[0040] Moreover, the anion exchange membrane of the present embodiment is an anion exchange membrane used for electrodialysis in a polar organic solvent, specifically, an anion exchange membrane used for electrodialysis of an aqueous solution containing a halide ion and a polar organic solvent. The anion exchange membrane that can be used in a polar organic solvent environment is the one described above as "sulfate ion (SO4 2- ) versus iodide ion (I - ) transmittance ratio (T I / T SO4 )" and / or the above "thickness swelling ratio."
[0041] In this specification, the SO4 index in an anion exchange membrane can be measured in accordance with the following seawater concentration test. <Seawater concentration test> Small electrodialysis device (current-carrying membrane area 100 cm 2 ) with a membrane resistance of 1.5 Ω cm 2 More than 2.5Ω cm 2 The following cation exchange membranes are used as a pair, and the monovalent selective surface of the anion exchange membrane to be evaluated is assembled so as to face the deionization compartment. The operating conditions were: 25°C seawater flowing through the desalination chamber at a flow rate of 6 cm / sec, the concentration chamber filled with 3.5 mol / L NaCl aqueous solution, and a current density of 3 A / dm 2 Electrodialysis was performed for 5 hours or more (until the concentration in the concentration compartment stopped changing), and the chloride ions (Cl - ) concentration (N) and sulfate ion (SO4 2- ) concentration(10 -3 The sulfate ion concentration thus obtained is taken as the SO4 index.
[0042] Here, the selectivity of monovalent anion and divalent anion permeation in a monovalent selective anion exchange membrane is as follows: Cl - On the other hand, SO4 was adopted as a divalent anion. 2- The selective permeability coefficients (P Cl SO4This is because monoselective anion exchange membranes are mainly used for concentrating seawater in the salt manufacturing industry, and in this application, the above-mentioned permselectivity coefficient (P Cl SO4 ) membrane, Cl - Therefore, even in the case of recovering iodine, if an anion exchange membrane with monovalent selectivity is used to avoid concentrating sulfate ions, the above Cl - and SO4 2- In the above-mentioned selective permeability defined in relation to the above, it is common to use a material having as small a physical property value as possible. However, according to the study by the present inventors, in iodine recovery, the selective permeability coefficient (P Cl SO4 If a membrane with a small diameter is used, the iodide ions and SO4 2- The permeation behavior of Cl - and SO4 2- It was found that there was an unexpected difference between the permeation rate of iodide ions and that iodide ions could not be concentrated at a sufficiently high permeation rate. Furthermore, when the research was carried out, it was found that, unexpectedly, when the "SO4 index" of the monovalent selective anion exchange membrane was used as an indicator of the permeability of iodide ions, it correlated well with the permeation amount of iodide ions, even though iodide ions are monovalent anions.
[0043] In this embodiment, the SO4 index can be controlled by appropriately selecting the type and amount of each component contained in the monovalent selective anion exchange membrane, the preparation method of the monovalent ion selective permeable layer, etc. Although details will be described later, for example, an element for setting the SO4 index in a desired numerical range is to appropriately control the density of the dense surface layer of the anion exchange membrane.
[0044] Here, the monovalent anion exchange membranes used to date have been used when it is desired to selectively permeate monovalent anions from a liquid to be treated that contains a mixture of monovalent anions and polyvalent anions, and therefore membranes with as high a monovalent selectivity as possible have been used. As a result, in the monovalent anion exchange membranes used to date, those with the smallest possible permeation amount when the SO4 index is measured have been used, specifically, 3.0×10 -3 In most cases, values below N were used.
[0045] In this situation, as described above, in the present invention, the SO4 index is 3.0×10 -3 N or more 50.0×10 -3 It is preferable to use a monovalent selective anion exchange membrane having an anion selectivity of N or less. The lower limit of the SO4 index in a monovalent selective anion exchange membrane is, for example, 3.0 x 10 -3 N or more, preferably 5.0×10 -3 N or more, preferably 6.0×10 -3 N or more. This can increase the efficiency of concentrating iodide ions during electrodialysis. Also, 6.0×10 -3 By setting the concentration to 1000 ppm or more, it is possible to suppress the decrease in the concentration efficiency of iodide ions even when electrodialysis is repeated. The reason for this is not entirely clear, but it is thought to be due to the interaction between iodide ions and the ion permeation channels in the membrane. On the other hand, the upper limit of the SO4 index in a monovalent selective anion exchange membrane is, for example, 50.0 × 10 -3 Less than or equal to 30.0×10 -3 N or less, preferably 20.0×10 -3 N or less. This makes it possible to suppress the concentration of divalent ions such as sulfate ions to a low level. In other words, the recovery ratio of iodide ions to multivalent ions such as divalent ions can be increased.
[0046] Here, the monovalent selective anion exchange membrane is an anion selective membrane that selectively selects SO4 2- Cl is more preferred than divalent ions such as- This refers to an anion exchange membrane that selectively allows the passage of monovalent ions such as SO4 2- and Cl - The selective permeability coefficient (P Cl SO4 Among them, those satisfying the prescribed value of the SO4 index are easily obtained. Therefore, in the monovalent selective anion exchange membrane used in the anion exchange membrane 7, the selective permeability coefficient (P Cl SO4 ) is preferably from 0.06 to 0.90, particularly preferably from 0.11 to 0.37.
[0047] Such anion monovalent selectivity can be imparted by forming a monovalent ion permselective layer on at least one surface of the anion exchange membrane. The specific configuration of the monovalent ion permselective layer is not particularly limited, but it is preferably at least one layer selected from the group consisting of a dense surface layer, an electrically neutral layer, and an oppositely charged layer. The "dense surface layer" is a layer in which the surface of the anion exchange membrane is formed with a dense structure (for example, a layer with a high degree of cross-linking or a layer with a high fixed ion concentration on the surface), the "electrically neutral layer" is a layer in which an electrically neutral thin layer that does not contain anion exchange groups is formed on the surface of the anion exchange membrane, and the "oppositely charged layer" is a thin layer with cation exchange groups formed on the surface of the anion exchange membrane.
[0048] The monovalent selective anion exchange membrane may be, for example, a base anion exchange membrane having an SO4 index of 3.0×10 on one or both sides. -3 N or more 50.0×10 -3The monovalent ion selective permeable layer can be formed in such an amount that the anion exchange membrane is 0.1 to 1.0 N or less. The monovalent ion selective permeable layer can be at least one layer selected from the group consisting of a dense surface layer, an electrically neutral layer, and an oppositely charged layer, but since it is easy to obtain an anion exchange membrane having a specified SO4 index, a dense surface layer is preferable, and in particular, a highly crosslinked resin layer formed using a divalent amine compound is preferable as the dense surface layer. As the base anion exchange membrane, a membrane in which a quaternary ammonium group, which is a strong basic anion exchange group, is introduced into the basic skeleton of a styrene-divinylbenzene copolymer is preferably used, because it has a strong structure and is easy to form a monovalent ion selective permeable layer.
[0049] These monovalent selective anion exchange membranes having an SO4 index that satisfies the above numerical range can be produced as follows. That is, a divalent amine compound is contacted with one or both surfaces of a raw membrane for introducing an anion exchange group obtained by polymerizing a polymerizable composition containing a styrene-based aromatic polymerizable monomer having a halogenoalkyl group and a crosslinkable polymerizable monomer such as divinylbenzene, and the membrane surface is coated with a divalent amine compound having an SO4 index of 3.0 x 10 -3 N or more 50.0×10 -3 N or less, a surface dense layer that is more highly cross-linked than the inside is formed, and then the remaining halogenoalkyl groups in the membrane are contacted with trialkylamine to convert them to quaternary ammonium groups. According to this method, a certain proportion of the halogenoalkyl groups present in the membrane surface portion on one side of the raw membrane for introducing anion exchange groups are consumed in cross-linking by contact with a divalent amine compound. Therefore, the membrane surface portion becomes denser due to cross-linking, and the SO4 2- Permeability to ions and the like decreases, and selectivity for monovalent anions is expressed.
[0050] In this method, the styrene-based aromatic polymerizable monomer having the halogenoalkyl group can be any known one without any restrictions. The alkyl group preferably has 1 to 8 carbon atoms, and the halogen atom substituted therewith can be chlorine, bromine, iodine, etc. Examples of such halogenoalkyl groups include chloromethyl group, bromomethyl group, iodomethyl group, chloroethyl group, bromoethyl group, iodoethyl group, chloropropyl group, bromopropyl group, iodopropyl group, chlorobutyl group, bromobutyl group, iodobutyl group, chloropentyl group, bromopentyl group, iodopentyl group, chlorohexyl group, bromohexyl group, iodohexyl group, etc. Specific examples of aromatic polymerizable monomers having such a halogenoalkyl group include chloromethylstyrene, bromomethylstyrene, iodomethylstyrene, chloroethylstyrene, bromoethylstyrene, iodoethylstyrene, chloropropylstyrene, bromopropylstyrene, iodopropylstyrene, chlorobutylstyrene, bromobutylstyrene, iodobutylstyrene, chloropentylstyrene, bromopentylstyrene, iodopentylstyrene, chlorohexylstyrene, bromohexylstyrene, and iodohexylstyrene. Of these, it is particularly preferable to use chloromethylstyrene, bromomethylstyrene, iodomethylstyrene, chloroethylstyrene, bromoethylstyrene, iodoethylstyrene, chloropropylstyrene, bromopropylstyrene, iodopropylstyrene, chlorobutylstyrene, bromobutylstyrene, and iodobutylstyrene.
[0051] The anion exchange group introduction raw membrane obtained by polymerizing the polymerizable composition has a halogenoalkyl group in the membrane derived from the aromatic polymerizable monomer having the halogenoalkyl group, and as described below, this is converted into an anion exchange group, that is, a quaternary ammonium group. The quaternary ammonium group is a strong basic group and is very excellent as an anion exchange group, but when the presence of an anion exchange group other than this is also desired, in addition to the aromatic polymerizable monomer having the halogenoalkyl group, a polymerizable monomer having another anion exchange group, or a polymerizable monomer having a functional group that can introduce another anion exchange group, may be used in combination with the polymerizable composition. Such anion exchange groups other than the quaternary ammonium group are not particularly limited as long as they are functional groups that can become positively charged in an aqueous solution, and examples thereof include primary to tertiary amino groups, pyridyl groups, imidazole groups, and quaternary pyridinium groups. In the polymerizable composition, the amount of these polymerizable monomers having other anion exchange groups, or polymerizable monomers having functional groups to which other anion exchange groups can be introduced, is not particularly limited, but is preferably 100 parts by mass or less, and more preferably 50 parts by mass or less, per 100 parts by mass of the aromatic polymerizable monomer having a halogenoalkyl group.
[0052] Furthermore, in addition to the polymerizable monomers for introducing anion exchange groups into the anion exchange membrane, the polymerizable composition may contain a polymerizable monomer that is not directly involved in the introduction of such an anion exchange membrane, in an amount of 150 parts by mass or less per 100 parts by mass of the aromatic polymerizable monomer having a halogenoalkyl group. Examples of such polymerizable monomers that are not directly involved in the introduction of anion exchange membrane include styrene, acrylonitrile, methylstyrene, ethylvinylbenzene, acrolein, methylvinylketone, vinylbiphenyl, etc.
[0053] In the polymerizable composition, the amount of the polymerizable monomer that is not directly involved in the introduction of these anion exchange membranes is not particularly limited, but is preferably 400 parts by mass or less, and more preferably 150 parts by mass or less, per 100 parts by mass of the aromatic polymerizable monomer having a halogenoalkyl group.
[0054] In the polymerizable composition, a crosslinkable polymerizable monomer is used to increase the density of the anion exchange membrane obtained and to increase the membrane strength. As the crosslinkable polymerizable monomer, a monomer used in the production of a conventionally known ion exchange membrane can be used without any particular limitation. Specifically, for example, m-, p- or o-divinylbenzene, divinylbiphenyl, divinylsulfone, butadiene, chloroprene, isoprene, trivinylbenzene, divinylnaphthalene, diallylamine, triallylamine, divinylpyridine, or a multifunctional vinylbenzyl compound having three or more vinylbenzyl groups as disclosed in JP-A-62-205153 and the like can be used.
[0055] If these crosslinkable polymerizable monomers are mixed in too much amount with respect to the styrene-based aromatic polymerizable monomer having a halogenoalkyl group, the ion exchange capacity of the anion exchange membrane decreases and the degree of crosslinking becomes too high, which increases the membrane resistance, and there is a possibility that the iodine concentration efficiency decreases. On the other hand, if the mixing ratio of the crosslinkable polymerizable monomer is too small, not only the strength of the membrane decreases, but also the density of the highly crosslinked resin layer provided on the membrane surface does not increase, and there is a possibility that sufficient monovalent selectivity cannot be obtained. For these reasons, it is preferable to mix 2 to 20 parts by mass, preferably 3 to 15 parts by mass, of the crosslinkable polymerizable monomer with respect to 100 parts by mass of the polymerizable monomer component consisting of the aromatic polymerizable monomer having a halogenoalkyl group and the above-mentioned other polymerizable monomers used in combination as necessary.
[0056] A polymerization initiator is usually blended in the polymerizable composition. The polymerization initiator may be any conventionally known one without any particular limitation, and may be appropriately selected in consideration of the substrate to be used, molding conditions, etc. Specific examples include p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, α,α'-bis(tert-butylperoxy-m-isopropyl)benzene, di-tert-butyl peroxide, tert-butyl hydroperoxide, di-tert-amyl peroxide, tert-butylcumyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane ... )Hexyne-3, cumene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, 2,5-dimethyl-2,5-dihydroperoxyhexane, 2,5-dimethyl-2,5-dihydroperoxyhexyne-3, benzoyl peroxide, methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, cyclohexane peroxide, methylcyclohexane peroxide, isobutyl peroxide, 2,4-dichlorobenzoyl peroxide, o-methylbenzoyl peroxide peroxide, bis-3,5,5-trimethylhexanoyl peroxide, lauroyl peroxide, p-chlorobenzoyl peroxide, 1,1-di-tert-butylperoxy-trimethylcyclohexane, 1,1-di-tert-butylperoxycyclohexane, 2,2-di-(tert-butylperoxy)-butane, 4,4-di-tert-butylperoxyvaleric acid-n-butyl ester, 2,4,4-trimethylpentylperoxy-phenoxyacetate, α-cumylperoxyneode Preferred are tert-butylperoxycanoate, tert-butylperoxyneodecanoate, tert-butylperoxypivalate, tert-butylperoxy-2-ethylhexanoate, tert-butylperoxyisobutyrate, di-tert-butylperoxyhexahydroterephthalate, di-tert-butylperoxyazelate, tert-butylperoxy-3,5,5-trimethylhexanoate, tert-butylperoxyacetate, and tert-butylperoxybenzoate.These may be added to the monomer paste alone or in combination of two or more. The amount of the polymerization initiator as described above is usually preferably 0.1 to 30 parts by mass, more preferably 1 to 10 parts by mass, based on 100 parts by mass of the above-mentioned polymerizable monomer component.
[0057] The polymerizable composition may further contain a matrix resin as a viscosity modifier, which can improve the coatability of the polymerizable composition and prevent dripping or the like when the composition is applied to a substrate. Examples of such matrix resins include polyvinyl chloride, chlorinated polyvinyl chloride, ethylene-vinyl chloride copolymers, vinyl chloride-based elastomers, chlorinated polyethylene, chlorosulfonated polyethylene, ethylene-propylene copolymers, saturated aliphatic hydrocarbon-based polymers such as polybutylene, styrene-based polymers such as styrene-butadiene copolymers, and copolymers of these with styrene-based monomers such as vinyltoluene, vinylxylene, chlorostyrene, chloromethylstyrene, α-methylstyrene, α-halogenated styrene, α,β,β'-trihalogenated styrene, monoolefins such as ethylene and butylene, and conjugated diolefins such as butadiene and isoprene. Styrene-butadiene rubber or hydrogenated rubber thereof, nitrile rubber or hydrogenated nitrile rubber thereof, pyridine rubber or hydrogenated rubber thereof, and styrene-based thermoplastic elastomers can also be suitably used. Here, the styrene-based thermoplastic elastomer refers to polystyrene polymer, styrene and polybutadiene, polyisoprene, vinyl polyisoprene, ethylene-butylene alternating copolymer, and ethylene-propylene alternating copolymer. For example, polystyrene-hydrogenated polybutadiene-polystyrene copolymer, polystyrene-(polyethylene / butylene rubber)-polystyrene copolymer, polystyrene-hydrogenated polyisoprene rubber-polystyrene copolymer, polystyrene-(polyethylene / propylene rubber)-polystyrene copolymer, polystyrene-polyethylene-(polyethylene / propylene rubber)-polystyrene copolymer, polystyrene-vinyl polyisoprene-polystyrene copolymer, etc. are exemplified. The molecular weight of such a matrix resin is not particularly limited, but is usually preferably in the range of 1,000 to 1,000,000, particularly 50,000 to 500,000. Moreover, such a matrix resin is blended in the polymerizable composition in an amount sufficient to ensure appropriate viscosity, depending on the molecular weight. For example, the amount is preferably 1 to 50 parts by mass, and more preferably 3 to 15 parts by mass, relative to 100 parts by mass of the above-mentioned polymerizable monomer component.
[0058] In addition to the various components described above, the polymerizable composition may contain, if necessary, a plasticizer such as dioctyl phthalate, dibutyl phthalate, tributyl phosphate, styrene oxide, or an alcohol ester of a fatty acid or an aromatic acid, an organic solvent, or the like.
[0059] It is also preferable to add a compound having one or more epoxy groups, such as styrene oxide or diethylene glycol diglycidyl ether, to the polymerizable composition so as to capture halogen gas or hydrogen halide gas generated by thermal decomposition of the styrene-based aromatic polymerizable monomer having a halogenoalkyl group.
[0060] The polymerizable composition consisting of the above-mentioned components is filled into the voids of the substrate as a reinforcing material, and then polymerized to obtain a base membrane for introducing anion exchange groups. As such a substrate, any known substrate for ion exchange membranes may be used, and generally, a support material having a porosity of 20 to 90%, more preferably 40 to 80%, more preferably 45 to 55% is used. Examples include woven fabrics, nonwoven fabrics, porous films, nets, etc. formed from polyvinyl chloride, polyolefin, etc. Among these, polyolefins such as polypropylene and polyethylene are particularly preferred in terms of affinity with ion exchange resins and chemical resistance, and polyethylene is particularly preferred. As the shape of the substrate, it is preferable to use a porous film in terms of increasing the efficiency of iodine concentration after the monovalent selectivity is imparted. The thickness of the substrate is generally selected from the range of 50 to 300 μm, and is preferably 70 to 250 μm from the viewpoint of membrane resistance and strength retention.
[0061] The method of filling the substrate with the polymerizable composition is not particularly limited. For example, the polymerizable composition may be applied or sprayed onto the substrate, or the substrate may be immersed in the polymerizable composition. When the polymerizable composition is in a paste form, it is preferably applied by coating. The application of the polymerizable composition into the substrate may be carried out by a known means such as a roll coater, a flow coater, a knife coater, a comma coater, a spray, or a dipping.
[0062] After the polymerizable composition is introduced into the substrate as described above, the substrates are laminated together with a release material having releasability so as to prevent the substrates from adhering to each other, and then the laminate is wound up on a roller and heated to carry out polymerization.
[0063] The release material has heat resistance sufficient to withstand polymerization and can be easily peeled off after polymerization. For example, polyolefins such as polypropylene, poly1-butene, poly4-methyl-1-pentene, or random or block copolymers of α-olefins such as ethylene, propylene, 1-butene, and 4-methyl-1-pentene, ethylene-vinyl compound copolymers such as ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, and ethylene-vinyl chloride copolymers, polyvinyl compounds such as polymethyl acrylate and polymethyl methacrylate, polyamides such as nylon 6, nylon 6-6, nylon 6-10, nylon 11, and nylon 12, thermoplastic polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, polycarbonate, polyphenylene oxide, and biodegradable resins such as polylactic acid, or mixtures thereof can be used, and such films may be biaxially stretched. That is, from the above films, an appropriate one may be selected according to the type of monomer component in the polymerizable composition and used as the release material. In particular, from the viewpoints of heat resistance and releasability, a polyester film such as polyethylene terephthalate (PET) is most suitable.
[0064] The pressure during polymerization may be either normal pressure or increased pressure, and is generally about 0.1 to 1.0 MPa. The polymerization temperature may be any temperature lower than the melting point of the base material, and is generally in the range of 40 to 130° C. That is, by carrying out polymerization by heating to this temperature range, a part of the base material is dissolved in the polymerizable composition, and polymerization is carried out in this state, and as a result, the bonding strength between the ion exchange resin and the base material can be increased, and the membrane strength and concentration efficiency can be further improved. The polymerization time varies depending on the polymerization temperature, etc., but is generally about 3 to 20 hours.
[0065] After the polymerizable composition is applied to the substrate as described above, the composition is heated to polymerize, and the base membrane for introducing anion exchange groups is obtained, which is made of a membranous polymer. In order to obtain the monovalent selective anion exchange membrane of the present invention, after the base membrane for introducing anion exchange groups is obtained as described above, a monovalent ion selective permeable layer made of a highly crosslinked resin layer is formed on the membrane surface before the anion exchange groups are introduced. This is carried out, for example, by contacting a divalent amine compound with one side of the membrane surface of the base membrane for introducing anion exchange groups. In other words, if a monovalent anion selective layer is formed only on one side of the base membrane for introducing anion exchange groups, the other side of the membrane surface is covered with a film or the like, and the membrane surface on the other side that is not covered with the film is contacted with a divalent amine compound to form a more highly crosslinked resin layer on the membrane surface than inside.
[0066] The amino group of the divalent amine compound can react with the halogenoalkyl group contained in the base membrane for introducing anion exchange groups, releasing hydrogen chloride and forming a C-N bond, which in the divalent amine compound reacts with two halogenoalkyl groups to form a cross-linked structure. The denser the cross-linked structure, the higher the membrane resistance, but the higher the monovalent anion selectivity, and the smaller the SO4 index. In addition, the cross-linking reaction by the divalent amine compound proceeds from the membrane surface to the inside, and the deeper the cross-linking, the higher the monovalent anion selectivity and the higher the membrane resistance. Examples of the secondary amine compound include dimethylamine, diethylamine, dipropylamine, dibutylamine, diethanolamine, etc. From the viewpoint of the balance between resistance and monovalent anion selectivity, the shorter the substituent, the better, and dimethylamine is preferred.
[0067] When the halogenoalkyl group on the surface of the anion-exchange-group-introduced raw membrane is crosslinked by contacting with a secondary amine compound solution, if the divalent amine compound diffuses too slowly into the anion-exchange-group-introduced raw membrane in an aqueous solution or if the solubility is poor, a part of the water may be replaced with an organic solvent to adjust the diffusion rate and improve the solubility. In this case, hydrophilic solvents such as methanol, ethanol, 1-propanol, 2-propanol, and acetone can be used as the organic solvent to replace water. The content of the organic solvent is preferably within 30% by mass, particularly 5 to 15% by mass, relative to the water.
[0068] The SO4 index is 3.0 x 10 -3 N or more 50.0×10 -3 In order to obtain an anion exchange membrane having an appropriate surface density layer for N or less, the conditions for contacting and reacting the secondary amine compound are particularly important, and for example, the concentration at which the secondary amine compound is dissolved is preferably 0.01 mol / L to 2 mol / L, and particularly preferably 0.03 mol / L to 1 mol / L. If the concentration is too low, the crosslinking reactivity of the halogenoalkyl group with the divalent amine compound decreases, the monovalent ion selectivity decreases, and it becomes difficult to make the SO4 index below the upper limit value. On the other hand, if the concentration is too high, the diffusion of the raw membrane for introducing anion exchange groups into the membrane is strengthened, the crosslinking depth becomes too deep, and the SO4 index becomes less than the predetermined value.
[0069] In addition, the reaction temperature during contact with the divalent amine compound is 20 to 50°C, and the reaction time is 1 to 24 hours. If the reaction temperature is less than 20°C and / or the reaction time is less than 1 hour, the crosslinking reaction of the halogenoalkyl group cannot be sufficiently carried out, and it becomes difficult to make the SO4 index equal to or less than the upper limit value. If the reaction temperature exceeds 50°C and / or the reaction time exceeds 24 hours, the diffusion of the anion exchange group introduction raw membrane into the membrane is strengthened, the crosslinking depth becomes too deep, and the SO4 index also becomes less than the predetermined value. After reacting the anion exchange group introduction raw membrane with the secondary amine compound, washing may be performed to remove excess secondary amine compound that was not used in the reaction.
[0070] The reaction between the divalent amine compound and the halogenoalkyl group as described above may stop at the reaction between the divalent amine and one halogenoalkyl group, and may not lead to crosslinking between the two halogenoalkyl groups. In such a case, it is preferable to carry out a process of treating with an alkaline aqueous solution (an alkaline aqueous solution treatment process) after the contact process with the divalent amine compound. Although the detailed reaction is not understood, it is presumed that the alkaline compound neutralizes the hydrogen chloride that is eliminated and generated when the divalent amine compound reacts with one halogenoalkyl group, thereby promoting the reaction with the second halogenoalkyl group. As the alkaline aqueous solution, known aqueous solutions such as an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, an aqueous barium hydroxide solution, and aqueous ammonia can be used. A strongly basic aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution is preferred because it enables the treatment to be carried out more efficiently. The alkaline aqueous solution may have a pH of 8 to 14 at 25° C., but preferably has a pH of 10 to 14 at 25° C., since this allows the treatment to be carried out more efficiently. The treatment temperature is preferably 50 to 70° C., more preferably 55 to 65° C. If the treatment temperature is less than 50° C., the treatment takes a long time, resulting in low productivity. If the temperature exceeds 70° C., the treatment becomes harsh, and there is a possibility that the amino compound that has reacted once may be liberated. The treatment time with the alkaline aqueous solution in this step may be 4 to 24 hours, preferably 6 to 12 hours, and more preferably 6 to 10 hours. If it is less than 4 hours, the treatment may be insufficient. If it exceeds 24 hours, the treatment becomes too harsh, and the electrical resistance increases.
[0071] Next, a step of introducing quaternary ammonium groups into the residual halogenoalkyl groups in the ion exchange group-introduced raw membrane after the alkaline aqueous solution treatment step is carried out using a tertiary amine compound (quaternary ammonium group introduction step). Examples of the tertiary amine compound include trimethylamine, triethylamine, N,N-dimethylpropylamine, and N-ethyl-N-methylbutylamine. From the viewpoint of resistance, trimethylamine is preferred. By contacting the membrane with an aqueous solution of a tertiary amine compound and introducing quaternary ammonium groups, the residual halogenoalkyl groups present in the membrane from the surface to the inside can be substituted without affecting the monovalent anion selective layer made of a highly cross-linked resin layer. The method for this can be the same as the usual method for introducing quaternary ammonium groups in the manufacture of anion exchange membranes.
[0072] By the above method, the SO4 index is 3.0×10 -3 N or more 50.0×10 -3 N or less, a monovalent selective anion exchange membrane is obtained. Furthermore, in order to exhibit appropriate permeability to iodide ions, the monovalent selective anion exchange membrane used in the present invention should have an anion exchange capacity of 0.5 to 4.0 meq / g-dry membrane, particularly 0.8 to 3.0 meq / g-dry membrane, a moisture content of 10 to 40%, preferably 25 to 35%, and an electrical resistance of 1.2 Ω cm. 2 3.0Ω cm or more 2 Less than or equal to 1.7 Ω cm, preferably 2 More than 2.5Ω cm 2 Less than or equal to 1.8 Ω cm, preferably less than 1.8 Ω cm 2 More than 2.4Ω cm 2 The thickness is adjusted to be in the range of 50 to 320 μm, particularly 70 to 280 μm. That is, in order to obtain such physical properties, the composition of the polymerizable composition (the amount or type of monomer component and crosslinking agent), the thickness of the base material, and the crosslinking reaction conditions by the divalent amine compound are appropriately set. In addition, the concentration of chloride ions (Cl - The permeation amount is usually 3.2 mol / L or more, preferably 3.5 mol / L or more.
[0073] The configuration of the method for operating the electrodialysis apparatus of this embodiment will be described in detail below.
[0074] In this embodiment, the halide ion may be, but is not limited to, an iodide ion, a chloride ion, a fluoride ion, a bromide ion, or the like. Among these, the iodide ion (I - In the following example, the case where iodide ions are used will be described.
[0075] Fig. 1 is a cross-sectional view showing a schematic example of the configuration of an electrodialysis device 1. Fig. 2 is a diagram showing a schematic example of the configuration of an iodine recovery system 100. Fig. 3 is a flow diagram showing an example of an iodine recovery process.
[0076] An example of a method for recovering iodine using the operating method of the electrodialysis apparatus of the present embodiment includes an electrodialysis step of separating an aqueous solution (waste liquid 10) containing iodide ions and a polar organic solvent into an iodine-containing concentrate (concentrate 20) and a desalted liquid (desalted liquid 30) using the electrodialysis apparatus 1 of FIG. 1.
[0077] The iodine recovery system 100 in FIG. 2 is sufficient if it is equipped with at least a facility for supplying waste liquid 10 to the electrodialysis apparatus 1, and further includes a facility for treating the concentrated liquid 20 and / or desalted liquid 30 produced in the electrodialysis apparatus 1.
[0078] The waste liquid 10 (raw liquid) is not particularly limited as long as it is a liquid containing at least an iodine component including an iodide salt and a polar organic solvent, but examples thereof include waste liquid discharged from the manufacturing process of a product containing an iodine component, waste liquid discharged during disposal of a product containing an iodine component, waste liquid discharged from a synthesis process using an iodine component as a reaction catalyst, waste liquid of a cleaning solution used for cleaning a manufacturing device using an iodine component, and the like.
[0079] Specific examples of raw materials for the waste liquid 10 include waste liquid, waste powder, and waste solids from the manufacturing process, manufacturing equipment, or waste materials of products containing iodine components such as polarizing films, contrast agents, disinfectants, and radiation-related materials, or waste liquid or waste solids containing iodine catalysts (organic iodine compounds or inorganic iodine compounds) used in chemical synthesis such as the synthesis of pharmaceuticals such as antibiotics and antiviral agents. These may be used alone or in combination of two or more.
[0080] The iodine component is, for example, iodide ion (I - ), and is defined as including one or more selected from the group consisting of iodine (I2), iodic acid (HIO3), periodic acid (HIO4), and iodides (including inorganic iodine compounds or organic iodine compounds) that have been subjected to reduction treatment. Here, the waste liquid derived from the raw materials contains iodine ions among the above iodine components, usually at 3% or more, preferably about 3% to 30%. Furthermore, these waste liquids contain sulfate ions at a concentration of 1 g / L or more and below the saturated solubility of sulfate, more generally about 20 to 50 g / L. Furthermore, solids containing iodine components usually contain about 30% to 99.8% iodine element by mass.
[0081] The waste liquid 10 may be used as is, but may be subjected to chemical or physical pretreatment such as pH adjustment, dilution, decomposition and removal of organic matter, if necessary.
[0082] As shown in Fig. 1, electrodialysis device 1 has a concentration compartment 2, a deionization compartment 3, an ion exchange membrane separating the concentration compartment 2 and the deionization compartment 3, an anode 4, a cathode 5, and a power source 6. Electrodialysis device 1 is not limited to the configuration shown in Fig. 1 and may have a known device configuration.
[0083] An electrode solution is supplied from an electrode solution tank (not shown) to the electrode chamber (anode chamber) containing the anode 4 and the electrode chamber (cathode chamber) containing the cathode 5. The anode chamber and the cathode chamber are disposed on either side of an electrodialysis cell composed of a concentration chamber 2 and a deionization chamber 3. When a current is applied to the anode 4 and the cathode 5 using a power source 6, electrodialysis begins in the electrodialysis cell. As the electrode solution, a known solution can be used, for example, an aqueous solution of sodium hydroxide, an aqueous solution of potassium hydroxide, an aqueous solution of sodium hydrogen sulfate, an aqueous solution of potassium sulfate, etc. However, when performing bipolar electrodialysis after electrodialysis, the electrode solution used in the electrodialysis device 1 is preferably one that does not contain sulfate.
[0084] In the electrodialysis cell, the concentrating compartments 2 and the deionizing compartments 3 are partitioned by ion exchange membranes (either anion exchange membrane 7 or a cation exchange membrane 8) and arranged alternately. The electrodialysis device 1 may have at least a configuration in which a deionization compartment 3, an anion exchange membrane 7, a concentration compartment 2, a cation exchange membrane 8, and a deionization compartment 3 are arranged in this order, and from the viewpoint of increasing the processing capacity, may have one or more concentration compartments 2, preferably two or more concentration compartments 2. The concentrating chamber 2 may contain an electrolyte before electrodialysis. The electrolyte may contain, for example, an aqueous solution of an inorganic salt having electrical conductivity. For example, ion-exchanged water may be used when the electrodialysis device 1 is used for the first time, and the previous concentrated solution may be used when the device is continuously used after being stopped and then restarted. In addition to such electrolytes, an aqueous solution of sodium chloride, an aqueous solution of potassium iodide, an aqueous solution of sodium iodide, or the like may be used. However, it is preferable that the electrolyte does not contain sulfate.
[0085] A specific example of the electrodialysis device 1 used for the above-mentioned electrodialysis has a number of gasket spacers (also called chamber frames) stacked between a pair of electrodes, with anion exchange membranes 7 or cation exchange membranes 8 sandwiched between adjacent chamber frames, such that the anion exchange membranes 7 and cation exchange membranes 8 are, in principle, arranged alternately as a whole, and an ion exchange chamber (current-carrying section) partitioned by the anion exchange membranes 7 and cation exchange membranes 8 is formed in each gasket. The ion exchange compartments are arranged such that the deionization compartment 3 is the compartment in which the cation exchange membrane 8 is located on the cathode 5 side and the anion exchange membrane 7 is located on the anode 4 side, and the concentration compartment 2 is the compartment in which the anion exchange membrane 7 is located on the cathode 5 side and the cation exchange membrane 8 is located on the anode 4 side, and the deionization compartments 3 and the concentration compartments 2 are arranged alternately. That is, when a current is applied while a treatment liquid (electrolyte liquid) is circulated and supplied to the deionization compartment 3, the cations in the treatment liquid supplied to the deionization compartment 3 pass through the cation exchange membrane 8 and migrate to the concentration compartment 2 on the adjacent cathode 5 side, and the anions in the treatment liquid pass through the anion exchange membrane and migrate to the concentration compartment 2 on the adjacent anode 4 side. In this way, when the treatment liquid is circulated and supplied to the deionization compartment 3, and at the same time a salt water solution is circulated to the concentration compartment 2, the treatment liquid is desalted and a concentrated liquid 20 with an increased salt concentration can be obtained. The method for fixing the laminate of these ion exchange chambers between the electrodes is preferably, but not limited to, a filter press.
[0086] In this embodiment, at least one or all of the anion exchange membranes 7 included in the electrodialysis device 1 are capable of absorbing the above-mentioned "sulfate ions (SO4 2- ) versus iodide ion (I - ) transmittance ratio (T I / T SO4 ) and / or an anion exchange membrane that satisfies the above-mentioned "thickness swelling ratio."
[0087] When the anion exchange membrane 7 contains an anion exchange membrane other than the above-mentioned anion exchange membrane, the other anion exchange membrane may be a known one. For example, a monovalent ion permselective anion exchange membrane, a fully permeable anion exchange membrane, or a high-strength alkali-resistant anion exchange membrane may be used, and a monovalent ion permselective anion exchange membrane is preferable.
[0088] There are no particular limitations on the cation exchange membrane 8, and a strongly acidic cation exchange membrane, a high-strength alkali-resistant cation exchange membrane, or the like can be used. A low-swelling cation exchange membrane may also be used. The cation exchange membrane 8 may also be a monovalent ion-selective cation exchange membrane, and more specifically, a cation exchange membrane in which a sulfonic acid group, which is a strongly acidic cation exchange group, is introduced into the basic skeleton of styrene-divinylbenzene can be used. As commercially available cation exchange membranes, Neosepta (registered trademark) CSE and Neosepta (registered trademark) CMB manufactured by Astom Corporation can be used.
[0089] An example of the operation of the electrodialysis device 1 during electrodialysis is as follows. When a direct current is applied between the anode 4 and the cathode 5 using a power source 6, iodide ions (I - ) passes through anion exchange membrane 7 and moves to concentration compartment 2, and cations (including at least one of monovalent cations such as alkali metal ions and divalent cations such as alkaline earth metal ions) in deionization compartment 3 on the other side pass through cation exchange membrane 8 and move to the same concentration compartment 2. In this concentration compartment 2, iodide salts such as potassium iodide (KI) are produced. A concentrate 20 containing iodide salts (iodine-containing concentrate) is obtained from concentration compartment 2. A deionized liquid 30 is obtained from deionization compartment 3.
[0090] Here, an example of a process flow up to the electrodialysis step in the iodine recovery method will be described with reference to Figs.
[0091] First, waste liquid 10 is stored in waste liquid tank 11 via line 12 (piping).
[0092] The waste liquid 10 in the waste liquid tank 11 may be subjected to the above-mentioned chemical or physical pretreatment. When the waste liquid 10 contains a boron component, a pH adjustment step may be performed before the electrodialysis step, in which the pH of the waste liquid 10 is adjusted to 9.5 or less, preferably 8 or less, and more preferably less than 7. When the pH of the waste liquid 10 is adjusted to 9.5 or less, most of the boric acid (H3BO3) is not dissociated and exists as molecules, so that even when electrodialysis is performed, the boric acid hardly moves and is discharged as it is into the desalted liquid 30. This allows the boron component and the iodine component in the waste liquid 10 to be separated efficiently.
[0093] When the waste liquid 10 is acidic (pH less than 7), it is preferable to adjust the pH of the waste liquid 10 to 3 or more. Since free iodine is generated, which may deteriorate the ion exchange membrane and reduce the efficiency of electrodialysis, this can suppress the generation of free iodine due to the air oxidation of iodide ions and prevent the deterioration of the ion exchange membrane due to the free iodine.
[0094] The lower limit of the temperature of the waste liquid 10 in the waste liquid tank 11 may be, for example, 25° C. or higher, preferably 30° C. or higher, and more preferably 35° C. or higher. By increasing the temperature of the waste liquid 10 supplied to the desalting compartment 3 in the electrodialysis apparatus 1, the efficiency of electrodialysis can be increased. The upper limit of the liquid temperature of the waste liquid 10 in the waste liquid tank 11 should be as high as possible within the range of the upper limit temperature that the device can tolerate, if there are restrictions on the device side. If the electrodialysis device 1 is equipped with PVC piping, the upper limit may be, for example, 40°C or lower.
[0095] Subsequently, the waste liquid 10 in the waste liquid tank 11 is supplied to the deionization chamber 3 of the electrodialysis device 1 via the line 13. A voltage is applied to the anode 4 and the cathode 5 to carry out electrodialysis (electrodialysis step). In the electrodialysis step, the concentration of iodide ions (halide ions) in the desalted liquid at the end point as determined by absorbance method may be, for example, 0.5 g / L or more and 5 g / L or less.
[0096] The desalted liquid 30 produced in the desalting compartment 3 by electrodialysis is recovered via a line 31. On the other hand, the concentrated liquid 20 produced in the concentrating compartment 2 by electrodialysis is recovered via a line 22.
[0097] At this time, at least a part of the desalted liquid 30 may be supplied to the waste liquid tank 11 via a line 32 branched off from the line 31, and a mixed desalted liquid obtained by mixing the desalted liquid 30 and the waste liquid 10 may be supplied again to the desalting chamber 3. In other words, the waste liquid 10 supplied to the desalting chamber 3 may contain the desalted liquid 30. By repeating the electrodialysis in this manner, the concentration of iodide ions in the desalted solution 30 can be reduced to a desired value.
[0098] On the other hand, at least a portion of the concentrated liquid 20 may be supplied to the concentrated liquid tank 21 via a line 23 branched off from the line 22, and the concentrated liquid 20 in the concentrated liquid tank 21 may be supplied again to the concentrating chamber 2 via a line 24. By repeating the electrodialysis in this manner, the iodide ion concentration in the concentrated solution 20 can be concentrated to a desired value.
[0099] In addition, when two or more electrodialysis devices are provided, a first concentrated solution produced from a first electrodialysis device may be supplied to a desalting compartment of a second electrodialysis device. Furthermore, a second desalted solution produced in the desalting compartment of the second electrodialysis device may be mixed with the first concentrated solution and supplied again to the desalting compartment of the second electrodialysis device.
[0100] Alternatively, an electrodialysis device 1 equipped with a continuous circulation type electrodialysis facility may be used. Such an electrodialysis apparatus 1 can be continuously operated by continuously supplying the waste liquid 10 or a mixed desalted liquid to the desalted liquid 30 while continuously discharging the desalted liquid 30.
[0101] Next, an example of a process flow of the regeneration step in the iodine recovery method will be described with reference to FIG.
[0102] Subsequently, the iodine recovery method can include a regeneration step of producing one or more selected from the group consisting of iodine (I2), iodide salts, and hydroiodic acid, using the iodine-containing concentrated liquid (concentrated liquid 20) obtained after the electrodialysis step, as shown in FIG. 3. The iodine, iodide salt, and hydroiodic acid regenerated (recycled) in the above-mentioned iodine recovery method may each be in the form of an aqueous solution, and the iodine and iodide salt may be in the form of a powder (including granules).
[0103] The iodine recovery method can recover hydroiodic acid using the obtained concentrated liquid 20. For example, as shown in Fig. 3, the iodine recovery method may include a step of separating the iodine-containing concentrated liquid (concentrated liquid 20) into hydroiodic acid and an aqueous hydroxide salt solution by bipolar membrane electrodialysis (bipolar electrodialysis step). Here, bipolar membrane electrodialysis is a method in which bipolar membranes that generate hydrogen ions and hydroxide ions, in addition to cation exchange membranes and / or anion exchange membranes, are arranged in sequence between an anode and a cathode, and a treatment liquid is supplied to each chamber separated by the membranes and an electric current is passed through to obtain an acid and an alkali from a neutral salt.
[0104] Specifically, the concentrated solution 20 (e.g., KI concentrated solution) discharged from the electrodialysis device 1 is introduced into the bipolar membrane electrodialysis device. If necessary, the concentrated solution 20 may be acidified by adjusting the pH to less than 7. When a direct current is applied to the bipolar membrane electrodialysis device, the iodide salt in the concentrated solution 20 is electrolyzed, and an aqueous solution of hydroiodic acid (HI solution) and an aqueous solution of hydroxide (e.g., KOH) are discharged. Thereafter, the HI solution is purified by distillation to obtain hydroiodic acid.
[0105] In addition, the iodine recovery method can recover iodine (I2) using the obtained concentrated liquid 20. As shown in FIG. 3, when a concentrated solution 20 containing iodide ions is oxidized, iodine (I2) is obtained.
[0106] The iodine recovery process can use the resulting concentrated solution 20 to recover iodide salts. As shown in Figure 3, when the hydroiodic acid obtained above is neutralized, an iodide salt is obtained. Also, when the iodine (I2) obtained above is reduced and neutralized, an iodide salt is obtained. In the iodine recovery method, the above-mentioned oxidation, neutralization, and reduction methods are not particularly limited, and known means can be used. The iodide salts include, for example, alkali metal iodide salts and alkaline earth metal iodide salts. Specific examples of iodide salts include potassium iodide, sodium iodide, calcium iodide, magnesium iodide, cesium iodide, etc. These may be used alone or in combination of two or more.
[0107] On the other hand, in the iodine recovery method, iodine (I2) can be recovered using the obtained desalted liquid 30. As shown in FIG. 3, the iodine recovery method may include a step of passing the obtained desalted liquid 30 through a strong basic anion exchange resin to adsorb iodide ions remaining in the desalted liquid 30 onto the strong basic anion exchange resin, and recovering iodine from the strong basic anion exchange resin.
[0108] Specifically, the desalted liquid 30 discharged from the electrodialysis device 1 is passed through a strongly basic ion exchange resin, and iodide ions are adsorbed on the strongly basic anion exchange resin. At this time, the pH of the desalted liquid 30 when passing through the strongly basic anion exchange resin is adjusted to less than 7, preferably 3 or more and less than 7, as in the above-mentioned electrodialysis. This makes it possible to selectively separate iodide salt ions by suppressing the adsorption of borate ions formed by dissociating boric acid onto the strongly basic anion exchange resin. Thereafter, iodine (I2) can be recovered from the strongly basic anion exchange resin by a known means.
[0109] Furthermore, when the waste liquid 10 contains a boron component, boron (B) can be recovered from the resulting desalted liquid 30 containing the boron component.
[0110] The iodine recovery method may include a boron recovery step of adjusting the pH of the desalted liquid 30 containing a boron component to, for example, 7 or more, preferably 8 or more, more preferably 11 or more, and then separating and recovering a boron-containing concentrate (boric acid concentrate) from the desalted liquid 30 using another electrodialysis device. When the boron-containing concentrate is acidified and crystallized, boric acid (H3BO3) can be recovered.
[0111] In addition, the desalted liquid 30 containing a boron component having a pH of 7 or more, or the desalted liquid 30 obtained when passing through the strongly basic anion exchange resin described above, is passed through a boron-selective chelating resin to adsorb boric acid ions. Thereafter, boric acid can be recovered from the boron-selective chelating resin by a known means.
[0112] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. Below, examples of reference forms are given. 1. A method for operating an electrodialysis apparatus, comprising an electrodialysis step of electrodialyzing an aqueous solution containing halide ions and a polar organic solvent using an electrodialysis apparatus equipped with an anion exchange membrane produced by a crosslinking polymerization method, The aqueous solution contains 200 mg / L or more of iodide ions, In the electrodialysis step, The anion exchange membrane includes an anion exchange membrane having a thickness swelling ratio of 104% or less, as measured according to the following measurement procedure. A method for operating an electrodialysis apparatus. (Measurement Procedure) The thickness of the anion exchange membrane was measured before and after immersion in a 50% by mass aqueous dimethylacetamide solution at a liquid temperature of 40° C. for 1 hour. The thickness before the treatment was designated D0, and the thickness after the treatment was designated D 50 Let us assume that. The obtained D0, D 50 The thickness expansion rate of the ion exchange membrane is calculated using the formula: (D 50 Calculate by: / D0) x 100. 2. A method for operating the electrodialysis apparatus according to 1., comprising the steps of: In the electrodialysis step, The electrodialysis apparatus is provided with a cation exchange membrane produced by a cross-linking polymerization method, The cation exchange membrane includes a cation exchange membrane having a thickness swelling ratio of 104% or less, as measured according to the measurement procedure. A method for operating an electrodialysis apparatus. 3. A method for operating an electrodialysis apparatus, comprising an electrodialysis step of electrodialyzing an aqueous solution containing halide ions and a polar organic solvent using an electrodialysis apparatus equipped with an anion exchange membrane produced by a crosslinking polymerization method, The aqueous solution contains 200 mg / L or more of iodide ions, In the electrodialysis step, When the anion exchange membrane was subjected to an electrodialysis test using a desalted solution containing iodide ions and sulfate ions, when the iodide ion residual rate in the desalted solution was 5%, the iodide ion (I - ) transmittance (%) is T I , sulfate ion (SO4 2- ) transmittance (%) is T SO4 When we define I / T SO4 The anion exchange membrane has a molecular weight of 3.5 or more. A method for operating an electrodialysis apparatus. 4. A method for operating the electrodialysis apparatus according to 3., comprising the steps of: In the electrodialysis step, A method for operating an electrodialysis apparatus, wherein the polar organic solvent contains a polar organic solvent having a relative dielectric constant of more than 30 at 25°C and / or a low dielectric organic solvent having a relative dielectric constant of 30 or less at 25°C. 5. A method for operating an electrodialysis apparatus, comprising an electrodialysis step of electrodialyzing an aqueous solution containing halide ions and a polar organic solvent using an electrodialysis apparatus equipped with an anion exchange membrane produced by a crosslinking polymerization method, The aqueous solution contains 200 mg / L or more of iodide ions, In the electrodialysis step, The polar organic solvent includes a polar organic solvent having a relative dielectric constant of 30 or less at 25°C. A method for operating an electrodialysis apparatus. 6. A method for operating the electrodialysis apparatus according to any one of 1. to 5., A method for operating an electrodialysis apparatus, wherein in the electrodialysis step, the concentration of halide ions in the desalted solution at the end point as determined by an absorbance method is 0.5 g / L or more and 5 g / L or less. 7. A method for operating the electrodialysis apparatus according to any one of 1. to 6., The method for operating an electrodialysis apparatus, wherein the aqueous solution contains 0.1% by mass to 50% by mass of the polar organic solvent. 8. A method for operating the electrodialysis apparatus according to any one of 1. to 7., The halide ion is an iodide ion (I - The method for operating an electrodialysis apparatus includes at least the steps of: 9. A method for operating the electrodialysis apparatus according to 8., comprising the steps of: The iodide ion (I - 2. A method for operating an electrodialysis apparatus, comprising the steps of: obtaining iodine (I2), iodic acid (HIO3), periodic acid (HIO4), and an iodine compound by reducing one or more of the following: 10. A method for operating the electrodialysis apparatus according to any one of 1. to 9., A method for operating an electrodialysis apparatus, wherein the anion exchange membrane comprises a base substrate containing a polyolefin and an ion-selective permeable layer formed on one or both sides of the base substrate. 11. A method for operating the electrodialysis apparatus according to any one of 1. to 10., In the electrodialysis step, The anion exchange membrane includes an anion exchange membrane having an ion exchange capacity change rate of within ±5% before and after immersion treatment in a polar organic solvent having a concentration of 50% by mass. A method for operating an electrodialysis apparatus. 12. A method for operating the electrodialysis apparatus according to any one of 1. to 11., comprising the steps of: In the electrodialysis step, The anion exchange membrane includes an anion exchange membrane having a water content change rate of within ±20% before and after immersion treatment in a polar organic solvent having a concentration of 50% by mass, as measured by the Karl Fischer method. A method for operating an electrodialysis apparatus. 13. An electrodialysis apparatus for electrodialyzing an aqueous solution containing halide ions and a polar organic solvent, comprising: A concentration chamber; A desalination chamber, The concentration compartment and the deionization compartment are separated by an anion exchange membrane and a cation exchange membrane produced by a cross-linking polymerization method, The aqueous solution contains 200 mg / L or more of iodide ions, The anion exchange membrane includes an anion exchange membrane having a thickness swelling ratio of 104% or less, as measured according to the following measurement procedure. Electrodialysis equipment. (Measurement Procedure) The thickness of the anion exchange membrane was measured before and after immersion in a 50% by mass aqueous dimethylacetamide solution at a liquid temperature of 40° C. for 1 hour. The thickness before the treatment was designated D0, and the thickness after the treatment was designated D 50 Let us assume that. The obtained D0, D 50 The thickness expansion rate of the ion exchange membrane is calculated using the formula: (D 50 Calculate by: / D0) x 100. EXAMPLES
[0113] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.
[0114] <Production of anion exchange membrane> (Anion exchange membrane A) 91.2 parts by mass of chloromethylstyrene, 5.0 parts by mass of divinylbenzene, 3.8 parts by mass of ethylvinylbenzene, 4.0 parts by mass of di-tert-butyl peroxide as a radical polymerization initiator, and 4.0 parts by mass of styrene oxide as a hydrogen chloride gas scavenger were added to obtain a paste-like polymerizable composition. Next, the polymerizable composition was applied to a biaxially stretched porous polyethylene film (thickness 100 μm, porosity 46%, average pore size 0.13 μm) serving as a substrate, to introduce the polymerizable composition into the substrate. Next, both sides of the substrate into which the polymerizable composition was introduced were covered with a release material made of a polyethylene terephthalate film and taken up on a roller, after which polymerization was carried out. The polymerization temperature pattern was to increase the temperature from 20°C to 50°C over 30 minutes, hold at 50°C for 20 minutes, then increase the temperature to 130°C over 80 minutes, and hold at 130°C for 4 hours to produce a base membrane for introducing anion exchange groups. Next, the release film was peeled off from the original membrane for introducing anion exchange groups, but at this time, the release material on both sides of the original membrane was not completely peeled off, but the release material was left on one side. This original membrane for introducing anion exchange groups, covered with the release material only on one side, was immersed in a 0.05 mol / L-dimethylamine aqueous solution for 5.5 hours at 34°C, and the chloromethyl groups on the surface not covered with the release material were crosslinked with dimethylamine. After that, the original membrane obtained was washed with a 1.0 mol / L-hydrochloric acid aqueous solution and pure water. Next, after removing the release agent film covering one side, the base membrane for introducing anion exchange groups was immersed in a 0.01 mol / L sodium hydroxide aqueous solution for 15 hours at 60° C. to carry out a process of treating with an alkaline aqueous solution. After that, the base membrane after the alkaline aqueous solution treatment was washed with pure water. Next, a quaternization reaction was carried out at 30°C for 16 hours using an aqueous solution containing 5% by mass of trimethylamine and 25% by mass of acetone, and the chlorine of the remaining chloromethyl groups in the membrane was replaced with trimethylamine to introduce quaternary ammonium groups. After that, the raw membrane after the introduction of the quaternary ammonium groups was washed using a 1.0 mol / L aqueous hydrochloric acid solution and pure water to obtain a monovalent selective anion exchange membrane.
[0115] (Anion exchange membrane B) A mixture of the following formulation was prepared: Styrene 33.2 parts by weight Divinylbenzene (purity 57%, the remainder is ethylvinylbenzene) 16.8 parts by mass Chloromethylstyrene 50.0 parts by mass Acetyl tributyl citrate 25.0 parts by mass Styrene oxide 3.4 parts by mass t-Butyl peroxy-2-ethylhexanoate (Perbutyl O, manufactured by Nippon Oil & Fats) 2.6 parts by mass To this mixture, 19.7 parts by mass of a hydrogenated styrene-butadiene block copolymer (product name: Tuftec M1913, manufactured by Asahi Kasei) having a polystyrene content of 30% by mass was added, and the mixture was stirred at 40° C. for 20 hours to obtain a homogeneous polymerizable composition. Next, the following high density polyethylene monofilament woven fabric was prepared. High density polyethylene monofilament woven fabric; Warp: 120 mesh - wire diameter 76μm (33 denier) Weft: 120 mesh - wire diameter 76μm (33 denier) Thickness: 132μm Opening ratio: 41% The polymerizable composition obtained above was applied onto the high density polyethylene monofilament woven fabric, and both sides were covered with polyester film as a release material, followed by polymerization at 70° C. for 5 hours. Next, the obtained membrane-like polymer was subjected to an amination reaction using an aqueous solution of 5 mass % trimethylamine and 25 mass % acetone at 30° C. for 16 hours to obtain an anion exchange membrane.
[0116] (Anion exchange membrane C) A base membrane for introducing anion exchange groups was produced in the same manner as in the anion exchange membrane A. Next, the release film was peeled off from the original membrane for introducing anion exchange groups, but at this time, the release material on both sides of the original membrane was not completely peeled off, but the release material was left on one side. This original membrane for introducing anion exchange groups, covered with the release material only on one side, was immersed in a 0.05 mol / L-dimethylamine aqueous solution for 10 hours at 34°C, and the chloromethyl groups on the surface not covered with the release material were crosslinked with dimethylamine. After that, the original membrane obtained was washed with a 1.0 mol / L-hydrochloric acid aqueous solution and pure water. Next, after removing the release agent film covering one side, the base membrane for introducing anion exchange groups was immersed in a 0.01 mol / L sodium hydroxide aqueous solution for 15 hours at 60° C. to carry out a process of treating with an alkaline aqueous solution. After that, the base membrane after the alkaline aqueous solution treatment was washed with pure water. Next, a quaternization reaction was carried out at 30°C for 16 hours using an aqueous solution containing 5% by mass of trimethylamine and 25% by mass of acetone, and the chlorine of the remaining chloromethyl groups in the membrane was replaced with trimethylamine to introduce quaternary ammonium groups. After that, the raw membrane after the introduction of the quaternary ammonium groups was washed using a 1.0 mol / L aqueous hydrochloric acid solution and pure water to obtain a monovalent selective anion exchange membrane.
[0117] <Thickness swelling rate> A 50% by mass aqueous solution of dimethylacetamide was placed in a glass container and heated in a water bath while stirring with a stirrer so that the temperature of the aqueous solution reached approximately 40°C. An ion exchange membrane was then added, and the temperature and stirring were continued. After one hour, the ion exchange membrane was removed. Using an optical microscope (KEYENCE, VHX-900F), the thickness of the ion exchange membrane before immersion in dimethylacetamide (D0) and the thickness of the ion exchange membrane after immersion in dimethylacetamide (D 50 ) was measured. The obtained D0, D 50 The thickness expansion rate of the ion exchange membrane is calculated using the formula: (D 50 / D0) × 100. The thickness expansion rate of the anion exchange membrane A was 101%. The thickness expansion rate of the anion exchange membrane B was 105%.
[0118] <Cl concentration test using seawater - and SO4 index> Small electrodialysis device (current-carrying membrane area 100 cm 2 ) and a monovalent selective cation exchange membrane CIMS (Astom Corporation, membrane resistance 2.0 Ω cm 2) was used as a pair and assembled with the sample anion exchange membrane so that the monovalent selective surface faced the desalting compartment. The operating conditions were: 25°C seawater flowing through the desalination chamber at a flow rate of 6 cm / sec, the concentration chamber filled with 3.5 mol / L NaCl aqueous solution, and a current density of 3 A / dm 2 Electrodialysis was performed for 5 hours or more (until the concentration in the concentration compartment stopped changing), and the chloride ions (Cl - ) and sulfate ion (SO4 2- The concentration of chloride ions (Cl - ) concentration (N) and sulfate ion (SO4 2- ) concentration(10 -3 The resulting chloride ions (Cl - ) concentration (N) and sulfate ion (SO4 2- ) concentration, Cl - The permeation rate and SO4 index were calculated. The SO4 index of anion exchange membrane A is 9.3 x 10 -3 It was N. The SO4 index of anion exchange membrane B is 82 x 10 -3 It was N. The SO4 index of anion exchange membrane C is 5.2 x 10 -3 It was N.
[0119] <Ion exchange capacity> (Immersion treatment) An organic solvent aqueous solution adjusted to a specified concentration was placed in a 300 mL glass container, and heated in a water bath while stirring with a stirrer so that the temperature of the organic solvent aqueous solution became 38°C to 40°C. The ion exchange membrane was then added, and the temperature and stirring were continued. After 1.5 hours, the ion exchange membrane was removed, and the organic solvent adhering to the surface was washed away with ion exchange water, and each measurement was performed. ·Soaking temperature: 38~40℃ Soaking time: 1.5 hours ·Immersion liquid volume: 200mL -Ion exchange membrane area: 25cm 2 ·Bath ratio: 25cm 2 / 200mL
[0120] (Procedure for measuring ion exchange capacity) Ion exchange membrane (area: 25 cm 2 ) was immersed in a 2 mol / L NaNO3 aqueous solution for 30 minutes, rinsed with water, and then immersed in a 2 mol / L NaCl aqueous solution for 1 hour, 1 hour, and 6 hours or more, with the solution being repeatedly renewed. After rinsing with water, the specimen was immersed in a 2 mol / L NaNO3 aqueous solution for 1 hour, 1 hour, and 6 hours or more, with the solution being repeatedly renewed. The immersion solution and the previous solution were titrated with a 0.1 mol / L-AgNO3 aqueous solution (indicator: K2CrO4), and the ion exchange capacity of the ion exchange membrane was measured before and after the above immersion treatment. In addition, when the ion exchange capacity before the immersion treatment was X1 and the ion exchange capacity after the immersion treatment was X2, the rate of change (%) of the ion exchange capacity before and after the immersion treatment was calculated from [(X2 / X1)-1]×100. When DMAc with a concentration of 50% by mass was used as the organic solvent aqueous solution for the above-mentioned immersion treatment, the rate of change in ion exchange capacity of anion exchange membrane A before and after the immersion treatment was -1%, 0% in DMF with a concentration of 50% by mass, and -2% in IPA with a concentration of 50% by mass.
[0121] <Moisture content> The weight of the ion exchange membrane was measured and recorded as the sample weight (g) before the immersion treatment. The ion exchange membrane (sample) thus immersed was sandwiched between Kimtowels, a 1 kg weight was placed on the sample, and the sample was left to stand for 1 minute. The sample was then cut and the moisture content was measured by the Karl Fischer method to obtain the moisture content (μg) of the sample. The moisture content was measured using a device manufactured by NITTOSEIKO, CA-31. Measurement was started 3 minutes after the sample was placed in the measuring device. The heating conditions for the measurement device were 180° C. and 20 minutes. The above moisture content measurement was carried out without placing a sample to obtain a blank value (μg). Using the above measurement results, the water content (mass%) of the ion exchange membrane after the immersion treatment was calculated based on "(water content of sample-blank test value) / weight of sample before the immersion treatment". The water content of the ion exchange membrane before the immersion treatment was also calculated in a similar manner by using the ion exchange membrane before the immersion treatment as a sample. In addition, when the moisture content before the immersion treatment was Y1 and the moisture content after the immersion treatment was Y2, the change rate (%) of the moisture content before and after the immersion treatment was calculated from [(Y2 / Y1)-1]×100. When IPA with a concentration of 50% by mass was used as the organic solvent aqueous solution for the above immersion treatment, the change in water content before and after the immersion treatment was -1% for anion exchange membrane A and more than -20% for anion exchange membrane B.
[0122] <Manufacture of electrodialysis equipment> The anion exchange membrane was placed in a tabletop test device (Micro Acilyzer (registered trademark) S3, manufactured by Astom Corporation) to assemble an electrodialysis device. Using the obtained electrodialysis device, an electrodialysis test was performed on each of the anion exchange membranes A and B produced above. The procedure for assembling the electrodialysis device will now be described in detail. First, an anion exchange membrane was punched out using a punching die made for a tabletop test device (hereinafter referred to as S3). Similarly, a polyolefin-based cation exchange membrane (the thickness expansion rate is 101%) was punched out. We prepared 12 ([1]-
[12] ) cation exchange membranes (hereinafter referred to as C membranes) and 10 ([1]-
[10] ) anion exchange membranes (hereinafter referred to as A membranes) that had been punched out. Using these, the following layers were stacked in the order of anode frame, end packing, C membrane [1], concentration compartment gasket, A membrane [1], deionization compartment gasket, C membrane [2], ..., C membrane
[10] , concentration compartment gasket, A membrane
[10] , deionization compartment gasket, C membrane
[11] , concentration compartment gasket, C membrane
[12] , end packing, and cathode frame. Spacer meshes were fitted into the current-carrying parts of the concentration compartment gasket and cathode compartment gasket. The A membrane was installed so that its selective surface faced the deionization compartment. Bolts were passed through the four corners of the frame and tightened to the specified torque to obtain the stack. The stack was inserted between the anode chamber and the cathode chamber and fixed to the main body by tightening the bolts at the four corners. S3 has three magnetic pumps built in, which connect the desalted liquid tank to the desalting chamber connection hole, and the concentrated chamber tank to the concentrated chamber connection hole, and then return to the original tank after passing through the stack. The third pump passes from the electrode solution tank to the cathode chamber and anode chamber in series and returns to the tank. If necessary, connect the piping to a heat exchanger, or place a cooler or heater in the tank to adjust the temperature. In this example, 1 mol / L-NaOH was used as the electrode solution. The anode and cathode plates were titanium plates coated with platinum. These electrodes were connected to a rectifier capable of supplying direct current.
[0123] (Evaluation of electrodialysis) A stock solution containing at least iodide ions, sulfide ions, and a polar organic solvent in its composition was supplied as a desalted solution to the desalting compartment of the electrodialysis apparatus assembled above. Pure water was used as the concentrated solution, and a 4% aqueous sodium hydroxide solution was used as the electrode solution. The content of each component in the desalted solution was measured at appropriate times from the start of electrodialysis until the residual ratio of iodide ions in the desalted solution reached 1%. The applied voltage was a constant voltage of 10 V. The relative dielectric constants of the polar organic solvents at 25°C are 19.9 for IPA, 37.8 for DMAc, and 36.7 for DMF, respectively.
[0124] In the electrodialysis of a desalted solution containing a polar organic solvent, the concentration of iodide ions (I - ) transmittance (%) is T I , sulfate ion (SO4 - ) transmittance (%) is T SO4 and iodide ion (I - ) transmittance ratio is T I / T SO4 Calculated from. At this time, T I (100%-5%), SO4 -was defined as (100% - "residual rate of sulfate ions in the desalted solution when the residual rate of iodide ions is 5%). 100% means the residual rate before electrodialysis. The measured values in Tables 1 and 2, T I and T SO4 Using the above "T I / T SO4 " he asked. For Example 3 and Comparative Example 2, the electrodialysis evaluation was performed three times, and the one with the highest IPA residual rate is shown in Table 2. It was confirmed that Comparative Example 2 had a larger difference between the maximum and minimum IPA residual rates and a larger variation in the values compared to Example 3. Iodide ions, chloride ions, and sulfate ions were quantified by ion chromatography. Sodium ions were quantified using an ICP emission spectrometer. Organic matter was quantified by measuring the total organic carbon concentration using a TOC meter and converting it into DMAc or IPA.
[0125] [Table 1] [Table 2] [Table 3] [Table 4]
[0126] As a result of the above (evaluation of electrodialysis), Examples 1 and 2 showed a higher residual rate of the polar organic solvent than Comparative Example 1, Example 3 showed less variation in the residual rate of the polar organic solvent than Comparative Example 2, and Example 4 showed a higher residual rate of the polar organic solvent than Comparative Example 2. From the above, it was found that in the electrodialysis method of each Example, the electrodialysis apparatus can be operated even in an environment where a polar organic solvent is contained in the desalted solution, and the selective permeability of halide ions to the polar organic solvent can be increased. It was found that, compared with Comparative Example 2, Examples 3 and 4 were able to selectively transmit iodide ions, among halide ions, while relatively leaving chloride ions behind. [Explanation of symbols]
[0127] 1 Electrodialysis equipment 2 Concentration chamber 3 Desalination room 4 Anode 5 cathode 6 Power supply 7 Anion exchange membrane 8. Cation exchange membrane 10 Waste liquid 11 Waste liquid tank 12, 13 lines 20 Concentrate 21 Concentrate tank 22, 23, 24 lines 30 Desalination solution 31, 32 lines 100 Iodine Recovery System
Claims
1. A method for operating an electrodialysis apparatus, comprising an electrodialysis step of electrodialyzing an aqueous solution containing halide ions and a polar organic solvent using an electrodialysis apparatus equipped with an anion exchange membrane produced by a crosslinking polymerization method, comprising the steps of: The aqueous solution contains 200 mg / L or more of iodide ions, In the electrodialysis step, When the anion exchange membrane was subjected to an electrodialysis test using a desalted solution containing iodide ions and sulfate ions, when the iodide ion residual rate in the desalted solution was 5%, the iodide ion (I - ) transmittance (%) is T I , sulfate ion (SO 4 2- ) transmittance (%) is T SO4 When defined as above, T I / T SO4 The anion exchange membrane has a molecular weight of 3.5 or more. A method for operating an electrodialysis apparatus.
2. A method for operating the electrodialysis apparatus according to claim 1, comprising the steps of: In the electrodialysis step, The method for operating an electrodialysis apparatus, wherein the polar organic solvent contains an organic solvent having a relative dielectric constant of 5 or more at 25°C.
3. A method for operating the electrodialysis apparatus according to claim 1 or 2, comprising the steps of: The aqueous solution contains 0.1% by mass to 50% by mass of the polar organic solvent.
4. A method for operating the electrodialysis apparatus according to claim 1 or 2, comprising the steps of: A method for operating an electrodialysis apparatus, wherein in the electrodialysis step, a concentration of halide ions in the desalted solution at the end point as determined by an absorbance method is 0.5 g / L or more and 5 g / L or less.
5. A method for operating the electrodialysis apparatus according to claim 1 or 2, comprising the steps of: The iodide ion is replaced by iodine (I 2 ), iodic acid (HIO 3 ), periodic acid (HIO 4 ), and iodine compounds, by reducing one or more of the compounds.
6. A method for operating the electrodialysis apparatus according to claim 1 or 2, comprising the steps of: A method for operating an electrodialysis apparatus, wherein the anion exchange membrane comprises a base substrate containing a polyolefin and an ion-selective permeable layer formed on one or both sides of the base substrate.
7. A method for operating the electrodialysis apparatus according to claim 1 or 2, comprising the steps of: In the electrodialysis step, The anion exchange membrane includes an anion exchange membrane having an ion exchange capacity change rate of within ±5% before and after immersion treatment in a polar organic solvent having a concentration of 50% by mass. A method for operating an electrodialysis apparatus.
8. A method for operating the electrodialysis apparatus according to claim 1 or 2, comprising the steps of: In the electrodialysis step, The anion exchange membrane includes an anion exchange membrane having a water content change rate of within ±20% before and after immersion treatment in isopropyl alcohol having a concentration of 50% by mass, as measured by the Karl Fischer method. A method for operating an electrodialysis apparatus.
9. A method for operating the electrodialysis apparatus according to claim 1 or 2, comprising: A method for operating an electrodialysis apparatus, wherein the content of the polar organic solvent in the aqueous solution is 1% by mass or more and 30% by mass or less.
10. A method for operating the electrodialysis apparatus according to claim 1 or 2, comprising: The method for operating an electrodialysis apparatus, wherein the polar organic solvent comprises one or more selected from the group consisting of alcohol-based solvents, amide-based solvents, ketone-based solvents, carboxylic acids having a total of 1 to 6 carbon atoms, glycol-based solvents, nitrile-based solvents, and sulfoxide-based solvents.
11. A method for operating the electrodialysis apparatus according to claim 1 or 2, comprising: The method for operating an electrodialysis apparatus, wherein the polar organic solvent comprises one or more selected from the group consisting of isopropanol (IPA), dimethylacetamide (DMAc), and dimethylformamide (DMF).
12. An electrodialysis apparatus for electrodialyzing an aqueous solution containing halide ions and a polar organic solvent, comprising: A concentration chamber; A desalination chamber, The concentration compartment and the deionization compartment are separated by an anion exchange membrane and a cation exchange membrane produced by a cross-linking polymerization method, The aqueous solution contains 200 mg / L or more of iodide ions, When the anion exchange membrane was subjected to an electrodialysis test using a desalted solution containing iodide ions and sulfate ions, when the iodide ion residual rate in the desalted solution was 5%, the iodide ion (I - ) transmittance (%) is T I , sulfate ion (SO 4 2- ) transmittance (%) is T SO4 When defined as above, T I / T SO4 The anion exchange membrane has a molecular weight of 3.5 or more. Electrodialysis equipment.
Citation Information
Patent Citations
Tokushuionkokantai
JP1976014887A
High-polymer composite having anion exchange power
JP1990056253A
Anion exchange membrane
JP2000212306A
Ion exchange membrane and method of manufacturing the same
JP2001157823A
Anion exchange membrane, method for producing the same and apparatus for treating solution
JP2002114854A